A Socio-Technical User Based Perspective for Urban Transport Solutions - The Fjordbus Case: udvidet resumé - Luengas, Camilo Andrés Perdomo (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
In the city of Aalborg, Denmark, several organisations have been working on the design of an autonomous passenger ferry (Fjordbus) to connect two urban areas separated by the sea. The Fjordbus is an ongoing technical innovation project coordinated by the Center for Logistik og Samarbejde (CLS) and partly sponsored by the Port of Aalborg and by the ShippingLab project. The primary purpose of the Fjordbus is to become a transport solution to connect the population of Aalborg and Nørresundby.